(untitled) (Bangladesh Journal of Pharmacology, 2016)
The present study was aimed to investigate the effect of bryostatin I on the expression of synuclein-A in breast cancer cells. Western blot analysis showed a significant (p<0.005) reduction in the expression of synuclein-A from a concentration of 20 µM in H3922 cells. The inhibitory effect of bryostatin I on synuclein-A expression was further confirmed by the treatment of H3922 cells with known synuclein-A inhibitor, cytokine oncostatin M. Bryostatin I treatment of H3922 cells also significantly increased their sensitivity to the taxol. Incubation of the cells with 25 µM concentration of bryostatin I followed by treatment with 0.5 ?M concentration of taxol induced apoptosis in 89% cells compared to 9% cells in the taxol alone treated cultures. Treatment of the H3922 cells with bryostatin I at 25 µM concentration led to a significant increase in the activation of histone H1 protein. The results from MTT assay showed a significant decrease in the cell viability from 10 µM concentration of bryostatin I. Thus, bryostatin I inhibits the growth of breast cancer cells through inhibition of synuclein-A expression and can be used for breast cancer treatment. Video Clip of Methodology: Cell viability assay: 5 min 14 sec Click to watch